2010
DOI: 10.1007/s00467-010-1679-7
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C, cardiometabolic risk, and body composition in severely obese children

Abstract: The aim of this study was to assess the relationship between cystatin C (CysC), cardiometabolic risk factors (CMRFs), and body composition in severely obese children. We evaluated 117 children aged 7-14 years old. Seventy-nine of these were severely obese (body mass index z-score ranging from 2.1 to 8.4), and 38 were children with normal nutrition state. CysC was determined by immunonephelometry. CMRFs (glucose, insulin, high-density lipoprotein cholesterol, triglycerides, homocysteine, uric acid, alanine amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
1
9
1
2
Order By: Relevance
“…29,30 Moreover, increased CysC values are associated with increased cardiovascular morbidity risk and atherosclerosis progression in both T1D patients and severely obese children. 31,32 Glomerular filtration rate (GFR) is best evaluated by the clearance of iohexol (iGFR). 32,33 Alternatively, in children, the 2009 modified Schwartz bedside GFR formula has been widely adopted because it has been strongly correlated to iGFR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 Moreover, increased CysC values are associated with increased cardiovascular morbidity risk and atherosclerosis progression in both T1D patients and severely obese children. 31,32 Glomerular filtration rate (GFR) is best evaluated by the clearance of iohexol (iGFR). 32,33 Alternatively, in children, the 2009 modified Schwartz bedside GFR formula has been widely adopted because it has been strongly correlated to iGFR.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Glomerular filtration rate (GFR) is best evaluated by the clearance of iohexol (iGFR). 32,33 Alternatively, in children, the 2009 modified Schwartz bedside GFR formula has been widely adopted because it has been strongly correlated to iGFR. 34,35 Moreover, formulas that assess both creatinine and cystatin C, like the Lund strategy (L-eGFR), 36 are considered to provide more accurate and reliable estimation of the GFR.…”
Section: Introductionmentioning
confidence: 99%
“…Though, studies in adults showed that CysC levels are increased in obese subjects (13,14) and that CysC-based formulas may result in an underestimation of GFR in patients with higher BMI (15). Few studies exist on CysC levels in children, leaving a large uncertainty regarding the influence of body composition in the interpretation of CysC levels (16).…”
mentioning
confidence: 99%
“…While many of these inflammatory markers and cytokines have been identified in animal models of obesity, they remain largely investigational and their clinical utility at this time is unknown. More clinically relevant, the impact of obesity on renal dysfunction has evolved with the identification of urinary cystatin C (Cys-C) as a correlate marker for glomerular filtration rate (GFR) [32,33]. While markers of inflammation including Cys-C were not evaluated in our cohort, we did identify an increased risk of renal toxicity based upon serum creatinine values in the obese patients.…”
Section: Discussionmentioning
confidence: 98%